Evolutionary history of the Tip100 transposon in the genus Ipomoea - Christoff, Ana-Paula (Sociedade Brasileira de Genética, 2012)
Tip100 is an Ac-like transposable element that belongs to the hAT superfamily. First discovered in Ipomoea purpurea (common morning glory), it was classified as an autonomous element capable of movement within the genome. As Tip100 data were already available in databases, the sequences of related elements in ten additional species of Ipomoea and five commercial varieties were isolated and analyzed. Evolutionary analysis based on sequence diversity in nuclear ribosomal Internal Transcribed Spacers (ITS), was also applied to compare the evolution of these elements with that of Tip100 in the Ipomoea genus. Tip100 sequences were found in I. purpurea, I. nil, I. indica and I. alba, all of which showed high levels of similarity. The results of phylogenetic analysis of transposon sequences were congruent with the phylogenetic topology obtained for ITS sequences, thereby demonstrating that Tip100 is restricted to a particular group of species within Ipomoea. We hypothesize that Tip100 was probably acquired from a common ancestor and has been transmitted vertically within this genus.